Geotechnical Characteristics of Volcanic Red Clay Soil Related to Geoengineering Problem in Sekincau, Sumatra, Indonesia - et al., Prahara Iqbal (International Journal of Advanced Science and Technology, 2020)
The study of physical, mechanical, and mineralogy characterization of volcanic red clay soilin the Sekincau Sub-District, West Lampung, Indonesia to obtain the genetic and soilengineering characterization related to the geoengineering problem. The method of this study isthe Geotechnical laboratory method, XRD, and SEM method. The results of the analysis showthat the volcanic red clay soil in the study area is residual soil produced from the weathering ofvolcanic rocks composed of felsic minerals in tropical environments. This soil is clayey silt(MH), loose, easily eroded, has the specific gravity 2.52 - 2.90, water content 27.21% - 67.14%,water saturation 72.98% - 94.75%, porosity 54.43% - 67.00%, the liquid limit value of 52.54-121.17%, a plasticity index value of 17.82-35.17%, permeability 7.4E-08 - 7.22E-05, hascohesion less than 1 Mpa, and an internal friction less than < 30o. Quartz, halloysite, kaolinite,and montmorillonite are the clay minerals that can be found in this soil. It can be concluded thatvolcanic red clay soil in the study area is easy to landslide during the rainy season.